Peran Hasil Hutan Bukan Kayu Dalam Mewujudkan Keberlanjutan Sumberdaya Hutan di Indonesia: Suatu Kajian Aksiologi Ilmu: The Role of Non-Timber Forest Products in Achieving Forest Resource Sustainability in Indonesia: An Axiological Study of Science - Wulandari, Febriana; Sarjan, Muhammad (HUTAN TROPIKA, 2024)
Non-timber forest products (NTFPs) are resources derived from forests other than timber, including plant-based products such as rattan, candlenuts, honey, bamboo, seeds, leaves, medicinal plants, and others, as well as animal-based products like wildlife and their parts (horns, skins, etc.). Forest management must prioritize benefiting local communities while maintaining ecological considerations. In Indonesia, NTFPs are estimated to account for 90% of the total economic value generated by forest ecosystems. However, in practice, the potential of NTFPs has not significantly contributed to improving the economy of communities around forest areas.NTFPs are often undervalued and treated merely as secondary forest products, partly due to the wide variety of NTFP types. This study uses a descriptive method. The findings conclude that NTFPs are a critical component in achieving sustainable forest management. Collaboration between the government, private sector, and communities is essential for the development of NTFPs. NTFP development must be rooted in the knowledge and practices of local communities. Identifying and mapping the potential of NTFPs forms the basis for planning their development and management strategies in alignment with forest conservation goals. The development of NTFPs should be based on local wisdom to preserve forest sustainability and strengthen local culture, ensuring that NTFPs become sustainable products